Research student and supervisor evaluation of intertextuality practices - Crocker, Jean; Shaw, Philip (HERMES - Journal of Language and Communication in Business, 2002)
Intertextuality is essential in academic writing but it is governed by quite complex conventions. Different intertextuality practices can be judged evidence of academic com-petence or incompetence, or condemned as plagiarism. Learners can break the conventions with criminal intent, or from ignorance, or because their language proficiency prevents them from doing anything else. This paper reports the results of interviews with academic staff in a British university and their postgraduate students about intertextuality practices. The interviewees ahowed a wide range of – sometimes contradictory – attitudes to quotation, referencing, and copying. Several pointed out the developmental advantages of various types of copying.